The Recruitment Criteria Of Sharia Committee Members Of Islamic Banks In Malaysia: An Analysis Based On Adab Al-Fatwa Wa Al-Mufti Wa Al-Mustafti By Al-Nawawi - Auwal, Salisu (2022)
The Sharia Committee is considered as one of the most important parts of the Sharia governance system in Islamic Financial Institutions (IFIs). They played many roles in the Islamic banking industry such as supervision, consultation, review of new products, fatwa issuance and many others within the IFIs. However, Sharia committee members (SCMs) are facing new issues and challenges that the development and improvement of a comprehensive Sharia governance framework seem to be needed today more than before. Thus, the institutionalization of Islamic fatwa in Malaysia became main factor of incorporating and developing its guidelines of recruitment and appointment criteria of SCMs based on al-Nawawiy’s thought and according to Sharia Governance Policy Document (SGPD2019) for having sufficient enough Sharia compliance in the Islamic banks (IBs) in Malaysia, as soon as it is institutionalized then the recruitment criteria of Islamic muftiys would be duly incorporated to SCMs of IBs. As such, this research is conducted to identify, analyze and conceptualize the qualities and qualifications of SCMs. A document research was reviewed, and content was analyzed with content analysis, also qualitative method was used in conducting interviews for Sharia officers, heads of Sharia committee, members of Sharia committees and academician with Islamic banking and finance background using purposive sampling.